Bifunctional Cyclam‐Based Ligands with Phosphorus Acid Pendant Moieties for Radiocopper Separation: Thermodynamic and Kinetic Studies. Issue 12 (3rd February 2015) - Paúrová, Monika; Havlíčková, Jana; Pospíšilová, Aneta; Vetrík, Miroslav; Císařová, Ivana; Stephan, Holger; Pietzsch, Hans‐Jürgen; Hrubý, Martin; Hermann, Petr; Kotek, Jan
Abstract Two macrocyclic ligands based on cyclam with trans‐disposed N‐methyl and N‐(4‐aminobenzyl) substituents as well as two methylphosphinic (H2L1) or methylphosphonic (H4L2) acid pendant arms were synthesised and investigated in solution. The ligands form stable complexes with transition metal ions. Both ligands show high thermodynamic selectivity for divalent copper over nickel(II) and zinc(II)—K(CuL) is larger than K(Ni/ZnL) by about seven orders of magnitude. Complexation is significantly faster for the phosphonate ligand H4L2, probably due to the stronger coordination ability of the more basic phosphonate groups, which efficiently bind the metal ion in an "out‐of‐cage" complex and thus accelerate its "in‐cage" binding. The rate of CuII complexation by the phosphinate ligand H2L1 is comparable to that of cyclam itself and its derivatives with non‐coordinating substituents. Acid‐assisted decomplexation of the copper(II) complexes is relatively fast (τ1/2=44 and 42 s in 1 M aq. HClO4 at 25 °C for H2L1 and H4L2, respectively). This combination of properties is convenient for selective copper removal/purification. Thus, the title ligands were employed in the preparation of ion‐selective resins for radiocopper(II) separation. Glycidyl methacrylate copolymer beads were modified with the ligands through a diazotisation reaction. The separation ability of the modified polymers was tested with cold copper(II) and non‐carrier‐added 64Cu in the presence of a large excess of both nickel(II) and zinc(II). The experiments exhibited high overall separation efficiency leading to 60–70 % recovery of radiocopper with high selectivity over the other metal ions, which were originally present in 900‐fold molar excess. The results showed that chelating resins with properly tuned selectivity of their complexing moieties can be employed for radiocopper separation.